Сценарії розвитку вугільної галузі при прогнозованих змінах структури використання вугільної продукції в економіці країни - Makarov V.M.; Perov M.O. (General Energy Institute of the National Academy of Sciences of Ukraine, 2022)
The article substantiates the forecast of economically feasible volumes of production of finished coal products in Ukraine, as well as its supply by the import to ensure the energy balance of the country while ensuring energy security of the state. To determine the potential of coal production in Ukraine, a mathematical model of optimization of the structure of extractive capacities of the coal industry was used. Taking into account the potential of coal production by state mines of Ukraine, scenarios for the development of the coal industry for the period up to 2040 have been developed, which taken into account the factors of occupation of part of the territory of Donbas and optimal strategies for industry modernization. Using the model of optimal supply of electricity to coal products, taking into account environmental constraints, the forecast calculations of providing the optimal structure of fuel of thermal power companies of Ukraine according to the basic and pessimistic scenarios of the coal industry. As a base of calculations is accepted the forecast of electricity production was developed by NEC Ukrenergo. Calculations have confirmed the possibility of satisfying the needs of thermal power plants with coal products of domestic production until 2040 at the current level of development of the coal industry. Taking into account the forecast of coal consumption in the country's economy and the potential for its production, forecast balances of coal products were developed according to the basic and pessimistic scenarios of Ukraine's coal industry development for a period until 2040. These balances take into account the volume of production of finished coal products in Ukraine, as well as its supply by imports, and it has been defined the export potential of the country.